PTK7-Targeting CAR T-Cells for the Treatment of Lung Cancer and Other Malignancies - Jie, Yamin; Liu, Guijun; Feng, Lina; Li, Ying; E, Mingyan; Wu, Liangliang; Li, Yinyin; Rong, Guanghua; Li, Yongwu; Wei, Huafeng; Gu, Anxin (Frontiers in Immunology, 2021)
In spite of impressive success in treating hematologic malignancies, adoptive therapy with chimeric antigen receptor modified T cells (CAR T) has not yet been effective in solid tumors, where identification of suitable tumor-specific antigens remains a major obstacle for CAR T-cell therapy due to the “on target off tumor” toxicity. Protein tyrosine kinase 7 (PTK7) is a member of the Wnt-related pseudokinases and identified as a highly expressed antigen enriched in cancer stem cells (CSCs) from multiple solid tumors, including but not limited to triple-negative breast cancer, non-small cell lung cancer, and ovarian cancer, suggesting it may serve as a promising tumor-specific target for CAR T-cell therapy. In this study, we constructed 3 different PTK7-specific CAR (PTK7-CAR1/2/3) each comprising a humanized PTK7-specific single chain variable fragment (scFv), hinge and transmembrane (TM) regions of the human CD8α molecule, 4-1BB intracellular co-stimulatory domain (BB-ICD), and CD3ζ intracellular domain (CD3ζ-ICD) sequence, and then prepared the CAR T cells by lenti-virus mediated transduction of human activated T cells accordingly, and sequentially evaluated their antigen-specific recognition and killing activity in vitro and in vivo.T cells transduced with all 3 PTK7-CAR candidates exhibited antigen-specific cytokine production and potent cytotoxicity against naturally expressing PTK7-positive tumor cells of multiple cancer types without mediating cytotoxicity of a panel of normal primary human cells; meanwhile, in vitro recursive cytotoxicity assays demonstrated that only PTK7-CAR2 modified T cells retained effective through multiple rounds of tumor challenge. Using in vivo xenograft models of lung cancers with different expression level of PTK7, systemic delivery of PTK7-CAR2 modified T cells significantly prevented tumor growth and prolonged overall survival of mice. Altogether, our results support PTK7 as a therapeutic target suitable for CAR T-cell therapy that could be applied for lung cancers and many other solid cancers with PTK7 overexpression.